(untitled) (Bangladesh Journal of Medical Science, 2017)
Introduction: Purifed CD34+ cells and cultured colony forming unit-granulocyte and macrophage (CFU-GM) from human bone marrow were utilized to examine the role of Fas/FasL and caspase-8interactionsin the regulation of myelopoiesis. Methods: Fas and FasL expression in CD34+ cells and in day 14 CFU-GM were measured by RTPCR and immunofluorescence in each case. The functional tests for the CFU-GM were the standard settlement test and the proliferative limit of CFU-GM was measured by replating the essential cells and monitoring auxiliary colony development. Results: Treatment of CFU-GM with IETD significantly increased, the proliferative limit, while the Fas mAb resulted in decreased the Fas and FasL expression were measuredutilizing RT-PCR and immunofluorescence individually. Conclusion: Fas, FasL, and caspase attenuationplay important rolesin the control of myelopoiesis. Bangladesh Journal of Medical Science Vol.16(1) 2017 p.122-126